ANALISIS SPASIAL KLOROFIL-A PERAIRAN PESISIR KOTA PAREPARE MENGGUNAKAN CITRA SENTINEL-2 - Prayitna, Yusri; Ihsan, Muhammad (Yayasan Nusantara Hasana Berdikari, 2026)
The coastal waters of Parepare City exhibited pronounced water quality dynamics during the 2024–2025 period, as reflected by fluctuations in the spatially averaged Normalized Difference Chlorophyll Index (NDCI) values ranging from −0.07 to 0.21. This study aims to analyze the spatial and temporal variability of chlorophyll-a in the coastal waters of Parepare using Sentinel-2 imagery and to evaluate the relationship between NDCI and bio-optical parameter estimates derived from the Case-2 Regional CoastColour (C2RCC) algorithm. The analysis was conducted using Google Earth Engine for NDCI computation and extreme-condition selection, accompanied by data quality filtering based on water-body masking and cloud screening. Two extreme conditions were identified, namely the HIGHEST condition on 14 January 2024 (mean NDCI = 0.2126) and the LOWEST condition on 28 May 2025 (mean NDCI = −0.0719), which were subsequently analyzed using the C2RCC algorithm applied to Sentinel-2 Level-1C imagery through the SNAP software. The results indicate that the coastal waters of Parepare exhibit typical Case-2 water characteristics, in which spatial variability in chlorophyll-a is generally associated with changes in Total Suspended Matter (TSM) driven by terrestrial material inputs. Although NDCI is effective as a relative indicator of chlorophyll-a variability, the occurrence of anomalies in littoral zones caused by mixed pixels highlights the necessity of integrating spectral indices with C2RCC based bio-optical estimates for robust monitoring of optically complex coastal waters.